Effectofhumanchorionicgonadotropinonpost-Ovulatory Mid-Lutealprofileand Subsequentpregnancy Ratein Anestrusbuffalousing Two Synchronization Regimes (Applied Biological Research, 2014)
The present study was aimed to assess the impact of post-insemination  human chorionic gonadotropin (hCG) administration on mid-luteal  functions and conception rate in Murrah buffalo. The study was conducted on 2 buffalo treatment groups viz., estradiol + controlled  internal drug releaser (CIDR) + gonadotropin releasing hormone  (GnRH, n = 27) and ovsynch + CIDR (n = 22). Half of the animals in  each group received intramuscular (i.m.) hCG (3000 IU, i.m.) on day 12  post-ovulation while groups served as control. The CG administration  on day 12 post-ovulation improved corpus luteum size and progesterone  level as well as first service conception rate after timed insemination in  buffaloes.
Keywords: Anestrus buffalo; conception rate; corpus luteum; endocrine profile; estrus synchronization; hCG